2019
DOI: 10.1111/pin.12829
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of non‐ampullary duodenal tumors and their phenotypic classification

Abstract: The tumorigenesis of non‐ampullary duodenal epithelial tumors (NADETs) might be different between the oral and anal sides of Vater's papilla. We conducted an immunohistological review to elucidate the clinicopathological features according to the tumor location and phenotypic classification. A review of an institutional database identified 121 patients with 125 superficial NADETs. NADETs were histologically evaluated and classified into the intestinal or gastric type based on immunohistochemical analysis. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 21 publications
(69 reference statements)
3
42
0
Order By: Relevance
“…Moreover, the incidence of SM invasion was higher among gastric‐type compared with intestinal‐type (28% vs 13%). All of the gastric type with SM invasion were located on the oral‐Vater and manifested as small lesions . These results including the present study lend support to the credence that NADCs may have several carcinogenesis pathways of different malignant potential depending on the location.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the incidence of SM invasion was higher among gastric‐type compared with intestinal‐type (28% vs 13%). All of the gastric type with SM invasion were located on the oral‐Vater and manifested as small lesions . These results including the present study lend support to the credence that NADCs may have several carcinogenesis pathways of different malignant potential depending on the location.…”
Section: Discussionsupporting
confidence: 86%
“…Unfortunately, immunohistochemical staining was not possible among all the cases included in this study because of the long study period (2005 to 2018). However, we have recently published another study in which immunohistochemical staining was performed among consecutive superficial non‐ampullary duodenal epithelial tumors during January 2010 to December 2016 . According to location analysis, the mucin phenotype was significantly different (oral‐Vater, gastric‐type 35%, intestinal‐type 65%; anal‐Vater, gastric‐type 13%, intestinal type 87%; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In general, histological diagnosis of mucosal duodenal cancer is made on the basis of features such as irregular nuclear size and shape, an increased nuclear:cytoplasmic (N/C) ratio, loss of polarity in nuclear arrangement, and structural abnormality [14]. In our present series, all cases of NAMDC showed a villous structure, disappearance of goblet cells, and loss of polarity.…”
Section: Discussionmentioning
confidence: 61%
“…It was reported recently that there is a close association between mucin phenotypes and clinicopathological features of NADETs. We and other investigators have shown correlations of the mucin phenotype of NADETs with tumor location, morphology, endoscopic findings and malignant potential,18,25,26 suggesting that the distinction of these two mucin phenotypes is clinically important. Furthermore, we are able to show in the present investigation that ME‐CV had higher diagnostic value than the WLE scoring system for NADETs of both gastric and intestinal phenotypes.…”
Section: Discussionmentioning
confidence: 69%